Development of duplex assembled I-shaped steel panel dampers. (November 2020) - Lin, Yu; Guo, Zhengxing; Yang, Sen; Guan, Dongzhi
Abstract: Shear steel panel dampers (SPDs) dissipate energy mainly by the shear yielding deformation of steel plates. Currently, most SPDs are fabricated from low-yield-point steel plates at high costs. However, the absence of adequate buckling restraints leads to large out-of-plane deformation of the shear panel. Further, achieving buckling restraint using welding stiffeners results in the premature failure of SPDs owing to weld damage. Therefore, this paper proposes a duplex assembled I-shaped steel panel damper (DAISPD) that is based on a Q235 hot-rolled H-beam. Webs are holed diagonally, and flanges on one side are cut while stiffeners are welded to the other side flanges, forming a channel-like steel energy dissipation unit. Two channel-like units are assembled back-to-back as a damper dissipating energy through the shear yielding. Quasi-static tests of five specimens were designed to investigate the properties of the DAISPD. Subsequently, to supplement the test results, numerical analysis was performed using Abaqus FEA software, focusing on critical parameters and energy dissipation capacity. The results indicate that for two kinds of configurations, where only stiffeners are adopted, and where both stiffeners and connectors are installed to constrain the buckling, the proposed solution effectively provides an adequate restraint to the buckling of the webs. The configuration where only stiffeners are adopted is recommended. Further, significant parameters of the recommended configuration are determined. Finally, a concept restoring force model is proposed, and a design method for the bearing capacity is proposed based on the results of physical tests and numerical analysis. Highlights: Two kinds of duplex assembled I-shaped steel panel dampers are elaborately studied. Based on the physical tests, the configuration only with stiffeners is suggested to enhance the hysteretic behavior. The kinematic hardening model is proved to be available in the numerical analysis of the duplex assembled I-shaped steel panel damper. Size of the weakened webs and layout of the weakening holes is proved to have significant influence on properties of the damper. Based on the physical tests and numerical analysis, a design method is suggested to estimate the ultimate restoring force.